THE RELIGION OF KALANG: MISTICAL-SYNTHESIS BETWEEN CULTURE OF KALANG AND ISLAM - Abdul Kholiq; Kiriana, Nyoman (UHN I Gusti Bagus Sugriwa Denpasar, 2026)
The main objective of this research is to explain the religious model of the Kalang after interacting with Islam. Islamic penetration of the Kalang raises the dialectic between the religion and culture of the Kalang. The Kalang have views and attitudes in the face of Islamization. This study used a qualitative method, focusing on the Kalang community in Poncorejo, Kendal. This study explains that the Kalang religion is constructed through a dialectical process between the Kalang belief system and Islam, with a rationalization that both can be reconciled without having to deny each other. His acceptance of Islam does not eliminate the Kalang tradition, which has been practiced for hundreds of years, but rather a pattern has developed by incorporating elements of Islam into its implementation. These symptoms, in turn, produce a hybrid culture as evidence of the occurrence of cultural reproduction in mystical-synthetic forms, such as adding Tahlil in the Obong ritual procession.